Overview of recent progress on steady state operation of all-metal plasma facing wall device QUEST. (June 2021) - Hanada, K.; Yoshida, N.; Hasegawa, M.; Oya, M.; Oya, Y.; Takagi, I.; Hatayama, A.; Shikama, T.; Idei, H.; Nagashima, Y.; Ikezoe, R.; Onchi, T.; et al.
Highlights: QUEST has been equipped with the hot wall to control fuel particle balance. The plasma pulse duration was longer after the installation of the hot wall. The model demonstrated the quantitative effect of the hot wall installation. The 6 h discharge was demonstrated. The presence of the unexplained hydrogen refill was confirmed during the 6 h discharge. Abstract: QUEST (Q-shu university experiment with steady state spherical tokamak) is a midsize spherical tokamak capable of steady-state operation, comprising all-metal plasma-facing walls and a hot wall (HW) to address issues pertaining to fuel particle balance. The HW was installed summer 2014. Quantitative analysis pertaining to the HW at 373 K is carried out, and clarify the quantitative impact of shot history that obviously appears in wall stored hydrogen just before the discharge at the wall temperature. The model indicates the plasma-induced deposition layer play an essential role in fuel particle balance. A clear temperature dependence of fuel recycling was observed using outgassing just after plasma termination and played an essential role in regulation of particle balance. Consequently, long duration discharges lasting more than 1 h has been obtained at wall temperature, TW  < 423 K in the range of 40–60 kW of RF power and, similarly, a 6 h discharge could be achieved at TW  = 473 K using 20 kW of injected RF power.